Answers

2014-08-24T22:51:11+08:00
Let    x  be the age of the daughter now
thus  the father age =  x+30    >  the father is 30 years older than the
                                                     daughter
and          x(x+30) = 736      > the product of their ages now
                 x²+30x =736
                 x²+30x-736 = 0
                 (x+46)(x-16) = 0
                 x = -46  or  16
thus the daughter age is    16 years now
& the father age is ( x + 30) =  16+ 30 = 46years now








0